[Editorial Review] Ethnomathematics in Educational Research Circles - Prabowo, Ardhi; Amidi, Amidi; Munahefi, Detalia Noriza (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
The development of ethnomathematical research is currently experiencing a fairly rapid increase in interest. This can be seen in the many ethnomathematical researches in the inaugural issue of Kreano, a creative-innovative mathematics journal, in English.Perkembangan riset etnomatematika saat ini mengalami peningkatan minat yang cukup pesat. Hal ini dapat dilihat pada banyaknya riset etnomatematika pada terbitan perdana Kreano, jurnal matematika kreatif-inovatif, dalam Bahasa inggris.